Spatial and temporal variations of geochemical and isotopic compositions of Paleozoic magmatic rocks in the Western Tianshan, NW China: A magmatic response of the Advancing and Retreating Subduction. (1st July 2022) - Tao, Zaili; Yin, Jiyuan; Sun, Min; Wang, Tao; Yuan, Chao; Chen, Wen; Huang, He; Seltmann, Reimar; Thomson, Stuart N.; Chen, Yuelong
Highlights: Two significant late Paleozoic magmatic "flare-up" events (ca. 340–355 Ma and 310–290 Ma) occurred in the West Tianshan. These magmatic activities reflect two stages of crust-mantle interaction in extensional settings. They recorded tectonic switching (advancing and retreating subduction) in ancient accretionary orogens. Abstract: The transition from advancing to retreating subduction is a fundamental process at convergent plate boundaries, recognition of which is critical to understand the tectonic evolution of the accretionary orogens. To explore subduction transition, this study presents an integrated study of zircon U-Pb age and bulk-rock geochemistry, as well as whole-rock Nd and zircon Hf-O isotopes for the late Paleozoic granitic rocks in the Western Tianshan of the southern Central Asian Orogenic Belt. The late Paleozoic granitic rocks consist mainly of early Carboniferous (∼344 Ma) I-type granites and late Carboniferous to early Permian (∼311–294 Ma) A-type granites. This magmatism reflects two stages of crust-mantle interaction that were probably formed in an extensional environment. Our data, combined with previous data, suggest that the magmatic rocks of the Western Tianshan originated from and emplaced within contrasting geotectonic settings causing crustal architecture to change variably in space and time. The simultaneous increase of (La/Yb)N ratios and decrease of εNd(t) values in the late Silurian to early Carboniferous and early to late Carboniferous correspond to two periods of advancing subduction, which led to two periods of magmatic lull in late Devonian and early to late Carboniferous. Conversely, the decrease of (La/Yb)N and increase of εNd(t) values in the early Carboniferous and late Carboniferous to early Permian record two periods of retreating subduction (slab roll-back). These episodes of retreating subduction of the South Tianshan Ocean possibly caused the formation of the Adengtao and Wusun Mountains back-arc basin and the coeval magmatic flare-up.